Beaming Sonny home - Pelletier, Cathie (New York : Washington Square Press, 1997)
When Mattie turns on the evening news to discover that her wayward son, Sonny, is the top story, she's afraid he might have shot the president and that would be "one little fracas she wouldn't be able to get him out of." It turns out that Sonny has not shot "that nice Mr. Clinton," but instead has taken two women and a poodle hostage in his ex-wife's trailer. Soon all of Maine and - thanks to CNN - folks across the country and world are glued to their TVs as the bizarre drama plays itself out. This is a memorable story that will make you laugh out loud, but ultimately Cathie Pelletier's gentle understanding of the dignity and pain inherent in the relationship between mother and child will haunt you.
Originally published: New York : Crown Publishers, 1996.
Maine author.
Keywords: Young men -- United States -- Psychology -- Fiction; Hostage negotiations -- United States -- Fiction; Mothers and sons -- United States -- Fiction; Psychological fiction; Domestic fiction; Humorous fiction